Pengaruh Profitabilitas, Deviden Payout Ratio, Struktur Modal Dan Cash Holding Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Konsumsi Di Bursa Efek Indonesia (BEI) - Nina Purnasari; Jimmy Rinaldo; Jessica Jessica; Carlina Harianto (Journal of Economic, Bussines and Accounting (COSTING), 2022)
In the all-digital era, it is very easy for people to participate in transactions in the capital market. Many people judge a company based on the high / low value of a company's shares. This research has a purpose as to examine the impact of profitability, dividend payout ratio, capital structure, & cash holding on the increase/decrease in company value. In this research that we made, we agreed to use quantitative research methods, the method is to collect numerical data (quantitative) and analyzed statistically, in this case we use the SPSS application. The data we use in this research is secondary data which is obtained through the Indonesia Stock Exchange (IDX) website or www.idx.co.id. The total cooperate that we researched are 12 consumer sector manufacturing companies. The period/year of the financial statements studied is 2017-2020 (4 years) as the total data is 48 data. The results of the research show that the value of X (Profitability, Dividend Payout Ratio, Capital Structure, and Cash Holding) has a significant impact on the value of Y (Company Value). Meanwhile, simultaneously, it shows that the value of X (Profitability, Dividend Payout Ratio, Capital Structure, and Cash Holding) has an insignificant positive/negative impact on Y (Company Value). Keywords : Profitability, Dividend payout ratio, Capital structure, Cash holding